Ecomodernist citizenship: rethinking political obligations in a climate-changed world. Issue 7 (3rd October 2018) - Symons, Jonathan; Karlsson, Rasmus
ABSTRACT: Green accounts of environmental citizenship typically seek to promote environmental sustainability and justice. However, some green theorists have argued that liberal freedoms are incompatible with preserving a planetary environment capable of meeting basic human needs and must be wound back. More recently, 'ecomodernists' have proposed that liberalism might be reconciled with environmental challenges through state-directed innovation focused on the provision of global public goods. Yet, they have not articulated an account of ecomodernist citizenship. This article seeks to advance the normative theory of ecomodernism by specifying an account of ecomodernist citizenship and subjecting the theory's core claims to sympathetic critique. We argue that state-directed innovation has the potential to reconcile ambitious mitigation with liberal freedoms. However, full implementation of ecomodernist ideals would require widespread embrace of ecophilic values, high-trust societies and acceptance of thick political obligations within both national and global communities. Ecomodernism's wider commitments to cosmopolitan egalitarianism and separation from nature thus amount to a non-liberal comprehensive public conception of the good. Furthermore, ecomodernism currently lacks an adequate account of how a society that successfully 'separates' from nature can nurture green values, or how vulnerable people's substantive freedoms will be protected during an era of worsening climate harms.